Internalization Of At-Ta'lim, At-Tarbiyah, At-Ta'dib Values In ‎Forming Students' Morals - Adinda Oktavia; Akhmad Syauqi Albaar‎; Wardatus Sholikha‎; Muhammad Yusron Maulana El-Yunusi (Wahana, 2024)
Lack of knowledge regarding students' morals towards teachers as teachers or as second parents in the school. The word "ta'lim" itself originates from the Arabic word and is an expression used to express education in ways including: 'Alamah, yu'allimu, and ta'lim". Ta'lim is defined as teaching, and yu'allimu is defined as teaching. Tarbiyah means "grow, increase, and height" in linguistics. In contrast, tarbiyah in sharia refers to charitable giving carried out through various channels and techniques that do not conflict with Islamic law. Ta'dib can be interpreted as how to educate or the process of educating, forming a person's morals and behavior according to the teachings of Islamic values ​​correctly and well. In the learning context, teachers are expected to be able to integrate these two concepts by providing good examples, guiding students in a loving way, and helping them become individuals who have good manners and in-depth knowledge. In this study, the author adopted a library research methodology because there are several consistent problems. a library research methodology because there are several consistent problems. Because there are at least several reasons underlying the author's use of the library research method. Firstly, the data source cannot be obtained from the field. Data sources in general can only be obtained through research or other written materials in the form of books, journals or other literature. The second is research or other written material in the form of books, journals or other literature. necessary as one of the few ways to understand a recent and difficult to understand phenomenon. Furthermore, using this study, the previously mentioned phenomena will be understood. Addressing emerging situations, the writer may formulate concepts to explain the emerging situation. Therefore, in responding to a situation that arises, the author can formulate a concept to explain the situation that arises. The third reason is that library data remains reliable for understanding researchers' problems. However, information or empirical data that has been collected by other people in the form of books, articles, or even research results can still be used, which can still be used by library researchers. Even in certain cases, field data is still not significant enough to answer the research questions to be carried out.